(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
Introduction: Menstrual hygiene management has not been satisfactorily addressed in developing countries due to insufficient WASH facilities. This results to poor health outcomes for adolescent school girls. The purpose of this study was to identify available WASH facilities affecting menstrual hygiene management among adolescent school girls in Chuka Sub County in Tharaka Nithi County. Methods: A cross-sectional study was conducted in Chuka Sub County, in Tharaka Nithi County among 383 adolescent school girls aged 10-19 years basically in secondary schools from December 2021 to March 2022. Data was collected using questionnaires then entered into Statistical Package for Social Science (SPSS) version 26 software and descriptive statistics was utilized for analysis. The results were presented in tables. Results: Majority of the girls reported availability of clean water at 94% (n=329), adequacy of clean water at 64% (n=224) separate toilets/ latrines at 94.6% (n=331),adequacy of toilets / latrine at 75.7% (n=265) privacy of toilet facilities at 78.3% (n=274) and cleanliness of the toilets/ latrines at 85% (n=297). Despite this, most of girls highlighted the toilets/ latrine lacked hand washing facilities at 52.9% (n=185). Conclusion: Most of the schools in Chuka Sub County had WASH facilities which included; sufficient clean water, separate latrines/toilets, privacy in toilets and clean toilets. Notably, some schools had unreliable hand washing facilities, which in turn negatively affected the menstrual hygiene of the students/ adolescent girls. Recommendation: The school administration should ensure that the hand washing facilities are installed at various designated areas for girls to use.